The Psychiatric Interview in Clinical Practice - MacKinnon, Roger A. (American Psychiatric Publishing, 2015)
This new, third edition maintains the book's reputation with thoroughly updated content that reflects changes brought about by the publication of DSM-5. The book presents the psychiatric interview in the context of the enormous and ongoing progress that has been made in biological and descriptive psychiatry.